2012
DOI: 10.1111/j.1551-2916.2011.05061.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Optical Properties of Free‐Standing Transparent Aluminum Nitride Film Assembled by Aligned Nanorods

Abstract: Free‐standing nanostructured Aluminum nitride (AlN) film with high transparence in visible light has been prepared by direct reaction of AlCl3 and NH3 through a thermal chemical vapor deposition method. The structural and morphological examinations reveal that the film is composed of a large number of well aligned wurtzite‐structured AlN nanorods with growth direction along the c‐axis. Raman scattering spectrum indicates the high alignment of the AlN nanorods, too. At room temperature, the nanostructured AlN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…As the EDX and XPS spectra in Fig. 2a and 2b confirmed the existence of O impurity, according to the literature, we believed that the violet emission at 357 nm of the un-doped sample (a) is originated from the transition between the separated oxygen substitution (O N ) ion the level and the aluminum-vacancy (O N V Al) complex level [14]. The emission peak at 438 nm of the sample (a) has been attributed to crystal native defects [15].…”
Section: Resultssupporting
confidence: 59%
“…As the EDX and XPS spectra in Fig. 2a and 2b confirmed the existence of O impurity, according to the literature, we believed that the violet emission at 357 nm of the un-doped sample (a) is originated from the transition between the separated oxygen substitution (O N ) ion the level and the aluminum-vacancy (O N V Al) complex level [14]. The emission peak at 438 nm of the sample (a) has been attributed to crystal native defects [15].…”
Section: Resultssupporting
confidence: 59%
“…PL spectrum of AlN whiskers was composed of two emission bands located at 405 and 510 nm, attributed to the nitrogen vacancy, was reported by Jiang et al (2011). Recently, Li et al (2012) reported a sharp ultraviolet emission at 358 nm from well-aligned wurtzite-structured AlN nanorods. Summing up from the former studies, it is still a challenge to achieve ultraviolet emission approaching the band gap in 1D AlN nanostructures because of O impurity, vacancy defects, and excessive surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…This particularly attractive material has attracted great research enthusiasm for fabricating AlN nanostructures and investigating their properties. Recently, one-dimensional (1-D) AlN nanostructures, such as nanorings, nanotubes and nanowires have been successfully fabricated by chemical vapor deposi-tion [6][7][8] , DC-arc discharge plasma method [9,10] , the direct nitridation method [11][12][13] , plasma process [14] and catalyst-assisted growth [15][16][17] . However, AlN nanostructures from those methods are synthesized at low temperature, which will inevitability induce defects, such as screw dislocations, stacking faults or mismatch between single-crystal components.…”
Section: Introductionmentioning
confidence: 99%